Inhibition of KCa3.1 Channels Suppresses Atrial Fibrillation via the Attenuation of Macrophage Pro-inflammatory Polarization in a Canine Model With Prolonged Rapid Atrial Pacing - He, Shanqing; Wang, Youcheng; Yao, Yajun; Cao, Zhen; Yin, Junkui; Zi, Liuliu; Chen, Huiyu; Fu, Yuntao; Wang, Xi; Zhao, Qingyan (Frontiers in Cardiovascular Medicine, 2021)
Aims: To investigate the role of KCa3.1 inhibition in macrophage pro-inflammatory polarization and vulnerability to atrial fibrillation (AF) in a canine model with prolonged rapid atrial pacing. Materials and Methods: Twenty beagle dogs (weighing 8 to 10 kg) were randomly assigned to a sham group (n=6), pacing group (n=7) and pacing+TRAM-34 group (n=7). An experimental model of AF was established by rapid pacing. TRAM-34 was administered to the Pacing+TRAM-34 group by slow intravenous injection (10 mg/kg), 3 times each day. After 7 days of pacing, the electrophysiology was measured in vivo. The levels of interleukin-1β (IL-β), monocyte chemotactic protein-1 (MCP-1), tumor necrosis factor-α (TNF-α), CD68, c-Fos, p38, and NF-κB p65 in both atriums were measured by Western blotting, and the levels of inducible nitric oxide synthase (iNOS) and arginase1 (Arg-1) were measured by real-time PCR. Macrophage and KCa3.1 in macrophage in the atrium were quantized following double labeled immunofluorescent. Results: Greater inducibility of AF, an extended duration of AF and lower atrial effective refractory period (AERP) were observed in the pacing group compared with those in the sham group. Both CD68-labeled macrophage and the expression of KCa3.1 in macrophage were elevated in the pacing group and inhibited by TRAM-34, led to higher iNOS expression, lower Arg-1 expression, elevated levels of IL-1β, MCP-1, and TNF-αin the atria, which could be reversed by TRAM-34 treatment (all P<0.01). KCa3.1 channels were possibly activated via the p38/AP-1/NF-κB signaling pathway. Conclusions: Inhibition of KCa3.1 suppresses vulnerability to AF by attenuating macrophage pro-inflammatory polarization and inflammatory cytokine secretion in a canine model with prolonged rapid atrial pacing.